The frequency of one-day abnormal returns and price fluctuations in the FOREX - Guglielmo Maria Caporale; Alex Plastun; Viktor Oliinyk (Journal of Applied Economics, 2021)
This paper analyses the explanatory power of the frequency of abnormal returns in the FOREX over the period 1994-2019. The following hypotheses are tested: frequency of abnormal returns is asignificant driver of price movements (H1); it does not exhibit seasonal patterns (H2); it is stable over time (H3). For our purposes avariety of statistical methods are applied including ADF, PP and KPSS tests, Granger causality tests, correlation analysis, regression analysis, Probit and Logit regression models. No evidence is found of either seasonal patterns or instability. However, there appears to be astrong positive (negative) relationship between returns in the FOREX and the frequency of positive (negative) abnormal returns. On the whole, the results suggest that the latter is an important driver of price dynamics in the FOREX, is informative about crises and can be the basis of profitable trading strategies, which is inconsistent with market efficiency.
Keywords: 330; anomalies; FOREX; frequency of abnormal returns; price dynamics